Determinant of Brand Equity on Customer Satisfaction and Loyalty: a Case Study of Kopi Kenangan, Ngagel Surabaya - Assalma Alhamdany, Savi Nadine; Winarno, Sri Tjondro; Mubarokah (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
This study examines the impact of brand equity on customer satisfaction and loyalty in Kopi Kenangan, Ngagel, Surabaya. This study used quantitative method to collect data from 50 respondents and analysed using SEM WarpPLS. The results of the study show that brand equity has a significant positive impact on customer satisfaction and loyalty, indicating that a strong brand can enhance customer experience and increase long-term loyalty. The study highlights the importance of brand equity as a key factor in customer retention and emphasises the contribution of brand image, perceived quality and brand awareness to satisfaction. These insights provide useful recommendations for coffee shop businesses to strengthen their brands and improve their relationships with customers, especially in a highly competitive market. By investing in brand equity, businesses can improve service quality, increase customer engagement and retain a loyal customer base. Overall, the study highlights the important role of brand equity in enhancing customer satisfaction and long-term business success.